Creating and Validating a Chemical Literacy Instrument Aligned Sustainability Contexts: Construct and Rasch Measurement Analysis - Hasanah, Samudra Mutiara; Rahayu*, Sri; Sulistina, Oktavia; Alsulami, Naif Mastoor (Universitas Syiah Kuala, 2025)
The connection between sustainability-based education and scientific literacy, particularly in the field of chemistry, is becoming increasingly significant. Therefore, a chemical literacy instrument needs to be integrated with sustainability contexts as a further development to equip students with a holistic understanding of the sustainable development goals. This study aims to create and validate a chemical literacy instrument aligned with sustainability contexts, focusing on atomic structure and periodic properties of elements. The instrument development process included item creation, content validation, and reliability analysis. The study involved chemistry education students from a university in Indonesia (N = 83). The instrument achieved expert validation with a validity index value of 0.95. Through Rasch analysis, 21 valid items with high reliability were identified, including 18 multiple-choice questions (r = 0.833) and 3 essay questions (r = 0.817). The instrument demonstrated effective distractor functionality, as well as acceptable values for the discrimination index, difficulty index, outfit mean square, and z-standardized. These results confirm the reliability and validity of the instrument in assessing chemical literacy within sustainability contexts, specifically focusing on good health and well-being. The instrument is recommended as a dependable tool for measuring chemical literacy in sustainability contexts. This research contributes to advancing chemical literacy to address global sustainability challenges